Immune response regulatory disorders and redox homeostasis in pregnant women with isoimmune conflict - Chernievskaya, S. G.; Moskalenko, T. Ya.; Rozhkovskaya, N. M.; Volianskaya, A. (Journal of Education, Health and Sport, 2017)
The immunological and biochemical changes caused by pregnancy may uncover new aspects of immune tolerance, applicable in physiological and pathological contexts, and show up new therapeutic strategies for improving pregnancy outcomes. Isoimmune conflict in pregnancy is primarily related to the risk of pre-natal fetal death caused by massive hemolysis when incompatible with Rh and / or AB0 antigens. The objective: The objective: to evaluate the role of redox homeostasis in the formation of the immune response in isoimmune conflict during pregnancy. Results. The results obtained indicate the activation of T- and B-lymphocytes, which may be explained by the activation of cytokines IL-1, IL-6, IL-10. In pregnancy isoimmune conflict moderate metabolic acidosis is observed with a predominance of the lactic acid component and the depletion of buffer reserves. Conclusions. Isoimmune conflict leads to moderate formation of oxidative stress, that can be described as violation of redox-homeostasis, which in turn can be a consequence of cytotoxic reactions.